Can D-dimer predict length of hospital stay in COVID-19 survivors? A cross-sectional study - Matthew Aldo Wijayanto; Risalina Myrtha; Dwi Rahayu; Graciella Angelica Lukas (Faculty of Nursing Universitas Padjadjaran, 2023)
Background: COVID-19 has been shown to increase the risk of thrombosis, where this mechanism occurs due to cell damage that triggers the release of various proinflammatory cytokines and chemokines, thereby activating the coagulation cascade. Thus, an increase D-dimer levels in COVID-19 patients occurs. The duration of patients' hospitalization, known as Length of Hospital Stay (LOS), plays a crucial role in enhancing patient care, reducing overall costs, and optimizing resource allocation. Purpose: The main objective of this study is to determine the correlation between D-dimer and various other factors to assess its predictive value for LOS) in COVID-19 survivors. Methods: This observational analytic study included COVID-19 patients who were admitted to Universitas Sebelas Maret Hospital in Sukoharjo, Indonesia, from November 2020 to January 2021. The data was taken from the medical records of patients diagnosed with COVID-19. Age, gender, comorbidities, admission oxygen saturation, D-dimer, neutrophil-lymphocyte ratio (NLR), haemoglobin, platelet count, white blood cells (WBC), LOS and estimated glomerular filtration rate (eGFR) were analysed in this study. Binary logistic regression was applied to determine the correlation between potential predictors on LOS. Results: A total 104 patients were included in the final analysis. The median LOS was 13 days (IQR 9-17 days). There was an increase of D-dimer in 79 patients with the median 759.39 ng/ml. Patients with prolonged LOS tend to have higher D-dimer levels (Median 924.95 vs 591.54 ng/ml, p = 0.018). However, D-dimer and other parameters was not associated with prolonged LOS in COVID-19 survivors (D-dimer p = 0.188; Age p = 0.138; Diabetes mellitus p = 0.172; NLR p = 0.859; Platelet count p = 0.097). Conclusions: D-dimer levels does not accurately predict prolonged LOS in COVID-19 survivors. Therefore, we suggest D-dimer solely should not be used as a tool to predict patient’s LOS.